(untitled) - Michael McCarthy (Cambridge, New York, 1991)
The book is a practical introduction to discourse analysis and its relevance for language teaching. It deals with new ways of looking at grammar, vocabulary and phonology in the light of discourse analysis. It concentrates on spoken and written language with examples from native-speaker and learner data. It also considers some teaching approaches based on the insignts of discourse analysis
Phân tích diễn ngôn trong giảng dạy ngôn ngữ
Keywords: language - discourse - analysis